From Form to Interaction: A Comparative Analysis of User Experience in Chinese and Western Chatbots - Hu, Ke; Xie, Jiahan; Zhao, Ying (Transactions on Social Science, Education and Humanities Research, 2024)
Chatbots have evolved into sophisticated conversational agents, significantly reshaping human-computer interaction through their ability to simulate human-like conversation. This paper explores the evolution of chatbots, focusing on third-generation agents capable of engaging in complex dialogues and grasping context. Traditionally, research has centered on evaluating the fidelity of chatbot communication and users’ perception of interaction quality. However, recent discourse has emphasized the importance of user experience (UX), including emotional resonance and contextual awareness. Cultural background has also emerged as a significant determinant of UX, necessitating an examination of cultural differences in chatbot interactions. This study investigates the interaction dynamics between non-anthropomorphic chatbots and users from diverse cultural backgrounds. Through empirical study, we reveal how cultural subtleties impact UX design principles and user approval, and we put forward ideas for cross-cultural optimization. Our research advances our knowledge of how chatbots engage with people from different cultural backgrounds and provides useful guidance for creating chatbots that are sensitive to cultural differences.